The Diagnostic Value of Systemic Immune-Inflammatory Index (SII) and Lymphocyte–Albumin–Neutrophil Ratio (LANR) in Chronic Obstructive Pulmonary Disease with Lung Cancer - Xu Y; Zhang L; Chen Z; Sun X; Zhao M; Wu Q; Hao J (Dove Medical Press, 2024)
Yidan Xu,1,* Lu Zhang,1,* Zhiyang Chen,1 Xiaonan Sun,1 Mengdan Zhao,1 Qirui Wu,2 Jiqing Hao1 1Department of Oncology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People's Republic of China; 2Fujian Institute of Research on the Structure of Matter, Chinese Academy of Sciences, Fuzhou, Fujian, People's Republic of China*These authors contributed equally to this workCorrespondence: Jiqing Hao, Department of Oncology, The First Affiliated Hospital of Anhui Medical University, 81 Meishan Road, Hefei, Anhui, People's Republic of China, Tel +86-13965029739, Email haojiqing@ahmu.edu.cnPurpose: This study aims to explore the association of inflammatory markers such as the Systemic Immune-Inflammatory Index (SII) and LANR with the comorbidity of Chronic Obstructive Pulmonary Disease (COPD) and lung cancer.Patients and Methods: A cross-sectional analysis was conducted on the clinical data of 309 patients with COPD only and 193 patients with COPD and lung cancer who attended the First Affiliated Hospital of Anhui Medical University. Additionally, we examined autonomous risk factors that contribute to the simultaneous development of COPD and lung cancer through univariate and multivariate logistic regression analyses. This analysis resulted in the development of a nomogram model for visual representation. The effectiveness of the model was assessed using a receiver operating characteristic (ROC) curve, calibration curve, and clinical decision analysis (DCA) curve, with internal validation conducted via repeated sampling methods.Results: Multivariate analysis of clinical characteristics and inflammatory markers showed that smoking history of > 60 pack-years, hemoptysis, emphysema, WBC count > 5.53 (× 10^9/L), SII > 629.285, and LANR < 11.39 were significantly associated with the comorbidity of COPD and lung cancer. These factors were subsequently integrated into the nomogram model. The AUC of the model stood at 0.849 (95% CI: 0.815- 0.882), demonstrating a notable improvement over the COPD-LUCSS scoring system (AUC: 0.716, 95% CI: 0.671- 0.761). The DCA curve indicated a notable clinical advantage provided by the model. Additionally, patients with stage IV tumors exhibited elevated SII levels and reduced LANR levels compared to earlier stages, indicating potential prognostic significance for both markers.Conclusion: Increased levels of the inflammatory markers SII and LANR are associated with the risk of comorbidity of COPD and lung cancer.Keywords: lung cancer, inflammation, systemic immune-inflammation index, nomogram, LANR, chronic obstructive pulmonary disease